Multi-dimensional outcomes following extracorporeal cardiopulmonary resuscitation - Tharusan Thevathasan; Vanessa Wahl; Joshua Boettel; Megan Kenny; Julia Paul; Sophie Selzer; Abdulla Al Harbi; Eva-Maria Dorsch; Heinrich Audebert; Matthias Rose; Christoph Paul Klapproth; Sonia Lech; et al. (Resuscitation Plus)
Background: Recent trials suggested that extracorporeal cardio-pulmonary resuscitation (ECPR) with veno-arterial extracorporeal membrane oxygenation (VA-ECMO) or “ECMELLA” (VA-ECMO plus Impella®) may improve short-term survival and neurological outcomes in selected patients with refractory cardiac arrest. However, long-term effects on cardiac, cognitive, physical and psychological health need further study. A multidisciplinary post-ECPR outpatient care program was developed at two centers, involving cardiologists, neurologists, psychologists and medical sociologists to assess seven key health dimensions. Methods: This bicentric, multidisciplinary study, conducted from May 2021 to April 2023, included adult ECPR survivors. Outcomes were assessed approximately 22 months post-cardiac arrest, focusing on cardiac, neurological, psychological and multi-organ functions, as well as social, professional and physical performance. Results: This study included 33 ECPR survivors, who were predominantly male (70%) with a mean age of 55 years. Left-ventricular ejection fraction improved significantly, from 22% during ICU stay to 51% at follow-up in the ECMELLA group and from 31% to 51% in the VA-ECMO group (p = 0.006). Many patients reported dizziness or dyspnea (>52%) during daily activities, with a median New York Heart Association class of 2, EQ-5D-5L score of 53 and elevated NT-proBNP levels. Despite normal neurological scores, 46% had memory issues, 39% struggled with daily organization, 52% had depression and 12% had suicidal thoughts. Physical performance was reduced, with a mean distance of 394 meters in the 6-minute walk test and a 6-minute bicycle ergometry time. Conclusion: ECPR patients showed significant improvement in left ventricular function over time but their neuropsychological and physical abilities remained compromised. Timely, multidisciplinary rehabilitation is required, starting in the intensive care unit and extending to include psychological support and community reintegration strategies after discharge.